The shadow economy—An expanding field of activity - Eckhardt Wohlers (Intereconomics, 1984)
The existence of a broad range of economic activities in the “shadow” of the official economy is nothing fundamentally new. However, there are signs that the shift into the shadow economy has been increasing considerably from the seventies onwards. Whereas growth in the “official” economy slowed down perceptibly, the shadow economy has clearly become a pronounced growth sector in the Federal Republic of Germany and in many other industrial countries.
Keywords: 330; Informal Economy